Work method control of Nigerian armed forces personnel: Roles of psychological detachment and conscientiousness. Issue 5 (3rd September 2022) - Ujoatuonu, Ikechukwu V. N.; Kanu, Gabriel C.; Okafor, Chiedozie O.; Okeke, Chidozie S.
Abstract : Our study investigated the moderating roles of psychological detachment and conscientiousness on work method control of the Nigerian armed forces. The study sample comprised 252 military personnel (female= 33%; mean age = 32.98 years, SD = 5.04 years). Hierarchical multiple regression analysis indicated psychological detachment to not moderate work method control. The interaction of conscientiousness and psychological detachment was associated with lower work method control. Conscientiousness, rather than work detachment, explained the military organisation's sense of work method control. Findings are consistent with the personality trait theory in understanding conscientiousness and its vital role in the well-being of security forces.